Comparative Analysis of a French Prospective Series of 144 Patients with Heparin-Induced Thrombocytopenia (FRIGTIH) and the Literature - Gruel, Yves; Vayne, Caroline; Rollin, Jérôme; Weber, Pierre; Faille, Dorothée; Bauters, Anne; Macchi, Laurent; Alhenc-Gelas, Martine; Lebreton, Aurélien; De Maistre, Emmanuel; Voisin, Sophie; Gouilleux-Gruart, Valérie; Perrin, Julien; Tardy-Poncet, Brigitte; Elalamy, Ismail; Lavenu-Bombled, Cécile; Mouton, Christine; Biron, Christine; Ternisien, Catherine; Nedelec-Gac, Fabienne; Duchemin, Jérôme; De Raucourt, Emmanuelle; Gouin-Thibault, Isabelle; Rugeri, Lucia; Tardy, Bernard; Giraudeau, Bruno; Bejan-Angoulvant, Théodora; Pouplard, Claire (Thrombosis and Haemostasis, 2020)
Background Heparin-induced thrombocytopenia (HIT) is a rare complication of heparin treatments, and only a few large patient cohorts have been reported. In this study, biological and clinical data from 144 French patients with HIT were analyzed in comparison with the literature.Methods The diagnosis of HIT was confirmed in all patients by an immunoassay combined with serotonin release assay. In the literature, only cohorts of at least 20 HIT patients published from 1992 were selected for a comparative analysis.Results Two-thirds of patients were hospitalized in surgery and most were treated with unfractionated heparin (83.2% vs. 16.8% with low molecular weight heparin only). Thrombotic events in 54 patients (39.7%) were mainly venous (41/54). However, arterial thrombosis was more frequent after cardiac surgery (13.2% vs. 2.4% in other surgeries, p = 0.042) with a shorter recovery time (median = 3 vs. 5 days, p < 0.001). The mortality rate was lower in our series than in the 22 selected published studies (median = 6.3% vs. 15.9%). Three genetic polymorphisms were also studied and homozygous subjects FcγRIIA RR were more frequent in patients with thrombosis (37.8 vs. 18.2% in those without thrombosis, p = 0.03).Conclusion This study shows that the mortality rate due to HIT has recently decreased in France, possibly due to earlier diagnosis and improved medical care. It also confirms the strong association between polymorphism FcγRIIA H131R and thrombosis in HIT.
Keywords: heparin; thrombocytopenia; thrombosis